Silicon Supplementation of Rescuegrass Reduces Herbivory by a Grasshopper - Mir, Showkat Hamid; Rashid, Irfan; Hussain, Barkat; Reshi, Zafar A.; Assad, Rezwana; Sofi, Irshad A. (Frontiers in Plant Science, 2019)
The theory of co-evolution suggests that herbivores play an important role in the diversification and composition of plant communities. A prevalent idea holds that grasses and grazing animals participated in an evolutionary ‘arms race’ as grassland ecosystems started spreading across the continents. In this race, besides other things, silicification in the form of phytoliths occurred in the grasses, and the graminivorous herbivores responded through specialized mandibles to feed on plants rich in phytoliths. It is important to understand whether these mandibles equip the herbivores in different environments or the grasses can augment their defense by channelizing their energy in high resource milieu. Here we used rescuegrass (Bromus catharticus; Family: Poaceae), an alien species of South America, to understand the mechanism of resistance offered by this species against a local insect herbivore (Oxya grandis; Family: Acrididae), graminivorous grasshopper, in different silicon rich environments. We used different concentrations of silicon and observed the types of phytoliths formed after Si amendments and studied the effect of phytoliths on mandible wear of the grasshopper. Silicon concentrations increased ca. 12 fold in the highest supplementation treatments. The results reveal that higher foliar silica concentration in Si rich plants did not result in changing the morphology of the phytoliths, still the leaf tissue consumption was lower in higher Si treatments, perhaps due to mandibular wear of the grasshoppers. The study opens a new dimension of investigating the role of Si amendments in reducing herbivory.